Neurobehavioral and Immunohistochemical Studies of the Cerebral Cortex Following Treatment with Ethyl Acetate Leaf Fraction of Tamarindus indica During Prenatal Aluminum Chloride Exposure in Wistar Rats - Usman IM; Adebisi SS; Musa SA; Iliya IA; Ochieng JJ; Ivang AE; Peter AB; Okesina AA (Dove Medical Press, 2022)
Ibe Michael Usman,1,2 Samuel Sunday Adebisi,1 Sunday Abraham Musa,1 Ibrahim Abdullahi Iliya,3 Juma John Ochieng,2 Andrew Ekpeyong Ivang,4 Akwu Bala Peter,2 Akeem Ayodeji Okesina2,5 1Department of Human Anatomy, Ahmadu Bello University, Zaria, Kaduna State, Nigeria; 2Department of Human Anatomy, Kampala International University, Bushenyi, Uganda; 3Department of Human Anatomy, Federal University Dutse, Dutse, Jigawa State, Nigeria; 4Department of Clinical Biology, University of Rwanda, Kigali, Rwanda; 5Department of Clinical Medicine and Community Health, University of Rwanda, Kigali, RwandaCorrespondence: Ibe Michael Usman, Tel +256706666798, Email gopama13@gmail.comPurpose: The recent increase in aluminum exposure and its effect on the development of the brain call for serious attention. The study investigated the behavioral and immunohistochemical changes in the cerebral cortex of Wistar rats following prenatal co-administration of ethyl acetate leaf fraction of Tamarindus indica (EATI) and aluminum chloride (AlCl3).Methods: Pregnant Wistar rats were divided into 5 groups (n=4). Group I (negative control), Group II-V were experimental groups treated with 200 mg/kg of AlCl3 s/c. Group III and IV received an additional 400 mg/kg and 800 mg/kg of EATI respectively, while Group V received an additional 300 mg/kg of Vitamin E for 14 days (prenatal days 7- 21) via the oral route. The pups were then exposed to cliff avoidance, negative geotaxis, and elevated plus maze (EPM) test on the post-natal day (PoND) 4- 6, 7- 10, and 18 respectively. On PoND 21 pups were sacrificed, and the skull dissected to remove the brain. The harvested brain tissues were processed for Cresyl fast (CF) and glial fibrillary acid protein (GFAP).Results: The study showed that EATI administration during AlCl3 exposure was associated with significant improvement in sensory-motor development. The EPM, CF, and GFAP results revealed significant improvement in anxiety-like behavior, motor activities, GFAP expression, pyramidal cell count, and Nissl staining following prenatal EATI administration during AlCl3 exposure.Conclusion: The present study concludes that EATI was associated with some protective potential during prenatal AlCl3 exposure in Wistar rats.Graphical Abstract: Keywords: Tamarindus indica, aluminum toxicity, glial fibrillary acid protein, sensory-motor development, elevated plus maze, anxiety-like behavior